Fun with ArcTan

Geometry Level 3

Find the sum of the solutions of the equation below

arctan ( 1 x ) + arctan ( 1 x + 2 ) = arctan ( 4 x + 3 ) \arctan \left( \frac{1}{x} \right) + \arctan \left( \frac{1}{x+2}\right) = \arctan \left( \frac{4}{x+3} \right)

5 \sqrt{5} 5 1 -10

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Patrick Zulkowski Staff
Jan 5, 2018

The key to this problem is the trig identity tan ( A + B ) = tan ( A ) + tan ( B ) 1 tan ( A ) tan ( B ) . \tan \left( A + B \right) = \frac{ \tan\left( A \right) + \tan \left( B \right) }{1- \tan\left( A \right) \tan\left( B \right) }. Since arctangent is the inverse of the tangent function, tan ( arctan ( 1 x ) + arctan ( 1 x + 2 ) ) = tan ( arctan ( 4 x + 3 ) ) = 4 x + 3 . \textcolor{#D61F06}{\tan} \left( \text{arctan} \left( \frac{1}{x} \right) + \text{arctan} \left( \frac{1}{x+2} \right) \right) = \textcolor{#D61F06}{\tan} \left( \text{arctan} \left( \frac{4}{x+3} \right) \right) = \frac{4}{x+3}. Using the trig identity, tan ( arctan ( 1 x ) + arctan ( 1 x + 2 ) ) = 1 x + 1 ( x + 2 ) 1 1 x 1 ( x + 2 ) = 2 ( x + 1 ) x 2 + 2 x 1 = 4 x + 3 \tan \left( \text{arctan} \left( \frac{1}{x} \right) + \text{arctan} \left( \frac{1}{x+2} \right) \right) = \frac{ \frac{1}{x} + \frac{1}{\left( x+2 \right)} }{1-\frac{1}{x}\frac{1}{\left( x+2 \right)}} = \frac{2 \left( x+1 \right)}{x^2+2x-1} = \frac{4}{x+3} after simplifying the complex fraction. After some algebra, we find x 2 5 = 0 , x^2-5=0, which has solutions ± 5 \pm \sqrt{5} . Only 5 \sqrt{5} is a valid solution, however.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...